2017
DOI: 10.18203/2394-6040.ijcmph20174808
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with level of birth preparedness among pregnant mothers at Kerugoya county referral hospital

Abstract: Background: Birth preparedness is the advance preparation made by an expectant mother which ensures access to skilled care. In Africa, the risk of pregnancy related deaths is 300 times more than in the developed world. In Kenya, out of 10 expectant mothers who access antenatal care services only 4 deliver in a health facility.Methods: This was a descriptive cross sectional study conducted at outpatient Maternal Child Health and Family Planning Clinic at Kerugoya County Hospital. The study utilized convenience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…This is contrary to a study done in Kirinyaga Kenya which found no association. 7 This could be attributed to the fact that a husband could be of support to the woman during pregnancy and therefore offer support in getting ready for the birth of the baby.…”
Section: Determinants Of Ibp Utilizationmentioning
confidence: 99%
See 4 more Smart Citations
“…This is contrary to a study done in Kirinyaga Kenya which found no association. 7 This could be attributed to the fact that a husband could be of support to the woman during pregnancy and therefore offer support in getting ready for the birth of the baby.…”
Section: Determinants Of Ibp Utilizationmentioning
confidence: 99%
“…Similar to other studies, we found that higher level of education is associated with birth preparedness and complication readiness. 6,7,[10][11][12][13][14] We attribute this to the fact that a woman who is educated is likely to understand more the health messages and apply the knowledge accordingly compared to an illiterate woman. 7,10,14 Contrary to studies in Kenya and Uganda, middle age rather than young age was associated with utilization of IBP.…”
Section: Determinants Of Ibp Utilizationmentioning
confidence: 99%
See 3 more Smart Citations